Utilization of polyphenylene sulfide as an organic additive to enhance gas separation performance in polysulfone membranes - Afdhal, Junaidi; Utari, Zulfiani; Siti, Khomariyah; Gunawan, Triyanda; Nurul, Widiastuti; Norazlianie, Sazali; Wan Norharyati, Wan Salleh (Royal Society of Chemistry, 2024)
Many studies have shown that sulfur-containing compounds significantly affect the solubility of carbon dioxide (CO2) in adsorption processes. However, limited attention has been devoted to incorporating organic fillers containing sulfur atoms into gas separation membrane matrices. This study addressed the gap by developing a new membrane using a polysulfone (PSf) polymer matrix and polyphenylene sulfide (PPs) filler material. This membrane could be used to separate mixtures of H2/CH4 and CO2/CH4 gases. Our study investigated the impact of various PPs loadings (1%, 5%, and 10% w/w) relative to PSf on membrane properties and gas separation efficiency. Comprehensive characterization techniques, including Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and scanning electron microscopy (SEM), were employed to understand how adding PPs and coating with polydimethylsiloxane (PDMS) changed the structure of our membranes. XRD and FTIR analysis revealed distinct morphological disparities and functional groups between pure PSf and PSf/PPs composite membranes. SEM results show an even distribution of PPs on the membrane surface. The impact of adding PPs on gas separation was significant. CO2 permeability increased by 376.19%, and H2 permeability improved by 191.25%. The membrane's gas selection ability significantly improved after coating the surface with PDMS. CO2/CH4 separation increased by 255.06% and H2/CH4 separation by 179.44%. We also considered the Findex to assess the overall performance of the membrane. The 5% and 10% PPs membranes were exceptional. Adding PPs to membrane technology may greatly enhance gas separation processes.